Body Mass Index Has a Linear Relationship with Cerebrospinal Fluid Pressure - John P. Berdahl; David Fleischman; Jana Zaydlarova; Sandra S. Stinnett; R. Rand Allingham; Michael P. Fautsch (2012)
To examine the relationship between body mass index (BMI) and cerebrospinal fluid pressure (CSFP), as low BMI and low CSFP have recently been described as risk factors for primary open-angle glaucoma (POAG).This was a retrospective review of the electronic medical records of patients who had CSFP measured by lumbar puncture and data to calculate BMI at the Mayo Clinic (Rochester, MN). Exclusion criteria included diagnoses, surgical procedures and medications known to affect CSFP. Mean CSFP for each unit BMI was calculated. The probabilities were two-tailed, and the α level was set at P < 0.05. Patients with documented BMI, CSFP, and intraocular pressure (IOP) were analyzed for the relationship between IOP and BMI.A total of 4235 patients, primarily of Caucasian descent, met the entry criteria. Median BMI was 26 and the mean CSFP was 10.9 ± 2.6 mm Hg. The increase in CSFP with increasing BMI was linear with an r(2) = 0.20 (P < 0.001). CSFP increased by 37.7% from BMI 18 (8.6 ± 2.1 mm Hg) to BMI 39 (14.1 ± 2.5 mm Hg). The r(2) (0.21) of the model of BMI and sex was similar to the r(2) of a BMI-only model (0.20). There was no relation between IOP and BMI within a subgroup of the study population (r (2) = 0.005; P = 0.14).CSFP has a positive, linear relationship with BMI. IOP is not influenced by BMI. If CSFP influences the risk for POAG, then individuals with a lower BMI may have an increased risk for developing POAG. Similarly, a higher BMI may be protective.